Tunable quantum gaps to decouple carrier and phonon transport leading to high-performance thermoelectrics - Yong Yu; Xiao Xu; Yan Wang; Baohai Jia; Shan Huang; Xiaobin Qiang; Bin Zhu; Peijian Lin; Binbin Jiang; Shixuan Liu; Xia Qi; Kefan Pan; et al. (Nature Communications, 2022)
Defects are believed to always scatter carriers. Here, the authors find that the quantum gaps in GeTe-based materials do not scatter carriers, which decouple the carriers and phonons transport leading to high thermoelectric performance.